An Analysis of Determinants of Loan Loss Provisioning Behaviour in Chinese Commercial Banks - Lin, Hanyu (2022)
This analysis examines loan loss provisioning behaviour of Chinese commercial banks over the period 2013–2020. We mainly test the income smoothing, capital management, and business cycle hypotheses. Meanwhile, cost efficiency estimates as another important variable are also included in the main model. The result supports the income smoothing motivation, the pro-cyclical trend of provisioning behaviour, and a positive correlation between cost efficiency and provisioning behaviour. However, this analysis does not find strong evidence of capital management hypothesis. Further research splits the sample depending on the ownership and size, and finds that the provisioning behaviour of state-owned banks shows counter-cyclicality, and large banks are more likely to utilize provisions to smooth income than small banks.